Alcuni temi arcaici presenti in Trebellius Pollio e in Flavius ​​Vopiscus - Gnoli, Tommaso (Lexis, 2020)
The analysis of many of the references to the ancient Republican past contained in the last lives of the Historia Augusta reveals that the unknown biographer was familiar with this context, even though, however, he was not very interested in it. His frequent allusions to specific episodes and events were mostly taken from Cicero and Livy, and were intended to colour the story and often to raise its tone, more often also with the aim to confuse and amaze the reader through multiple ioca. Among other things, also the events of the alleged censorship of Valerianus and the hypothetical interregnum after Aurelianus’ death are focused on.